Aligning care with the personal values of patients with complex care needs. (25th August 2021) - Tuzzio, Leah; Berry, Andrew L.; Gleason, Kathy; Barrow, Jennifer; Bayliss, Elizabeth A.; Gray, Marlaine Figueroa; Delate, Thomas; Bermet, Zoe; Uratsu, Connie S.; Grant, Richard W.; Ralston, James D.
Abstract: Objective: To identify opportunities to align care with the personal values of patients from three distinct groups with complex medical, behavioral, and social needs. Data Sources/Study Setting: Between June and August 2019, we conducted semi‐structured interviews with individuals with complex care needs in two integrated health care delivery systems. Study Design: Qualitative study using semi‐structured interviews. Data Collection Methods: We interviewed three groups of patients at Kaiser Permanente Washington and Kaiser Permanente Colorado representing three distinct profiles of complex care needs: Group A ("obesity, opioid prescription, and low‐resourced neighborhood"), Group B ("older, high medical morbidity, emergency department, and hospital use"), and Group C ("older, mental and physical health concerns, and low‐resourced neighborhood"). These profiles were identified based on prior work and prioritized by internal primary care stakeholders. Interview transcripts were analyzed using thematic analysis. Principal Findings: Twenty‐four patients participated; eight from each complex needs profile. Mean age across groups was 71 (range 48–86) years. We identified five themes common across the three groups that captured patients' views regarding values‐aligned care. These themes focused on the importance of care teams exploring and acknowledging a patient's values, providing access to nonphysician providers who have different perspectives on care delivery, offering values‐aligned mental health care, ensuring connection to community‐based resources that support values and address needs, and providing care that supports the patient plus their family and caregivers. Conclusions: Our results suggest several opportunities to improve how care is delivered to patients with different complex medical, behavioral, and social needs. Future research is needed to better understand how to incorporate these opportunities into health care.